Penerapan CRISP-DM dalam Klasifikasi Sentimen dan Analisis Perilaku Pembelian Layanan Akomodasi Hotel Berbasis Algoritma Decision Tree (DT) - Yerik Afrianto Singgalen (Jurnal Sistem Komputer dan Informatika (JSON), 2023)
The Cross-Industry Standard Process for Data Mining (CRISP-DM) approach is very relevant in identifying business challenges and producing recommendations in the form of appropriate models to face various business challenges. Sentiment classification is needed to identify and analyze consumer trends and preferences in order to plan risk mitigation strategies related to business sustainability. This study adopts the CRISP-DM method in classifying hotel guest sentiment through review data on the Agoda platform and analyzing sentiment data based on the purchase behavior of related products and services. Meanwhile, the stages in the CRISP-DM method are as follows: the stage of understanding the business context (business understanding), the stage of understanding data characteristics (data understanding), the modeling stage (modeling), the evaluation stage, and the implementation stage (deployment). The results of this study show that ten words are the attention of hotel guests and are dominated by positive sentiment, namely shopping, great, stay staff, clean, location, room, good, mall, and hotel. The classification results using the DT algorithm showed good performance with an accuracy value of 93.91%, a precision value of 90.98%, and a recall value of 97.77%. Â In addition, the AUC value is 0.943 or 94.3%, and the f-measure value is 94.18%. Furthermore, sentiment analysis data can be developed into a Customer Relationship Management (CRM) Â supporting application to analyze guest purchase history data related to sentiment, country of origin, guest type, room type, and length of stay by day, month, and year. Thus, the marketing strategy of hotel accommodation services can be optimized for personalization and increase interest and intention of returning stays.